Cation Effect of Bio‐Ionic Liquid‐Based Electrolytes on the Performance of Zn‐Ion Capacitors - Sumana Brahma; Jonathan Huddleston; Abhishek Lahiri (ChemElectroChem)
Abstract Zn‐ion capacitors (ZICs) are emerging as promising energy storage devices due to their low cost. Currently, aqueous‐based electrolytes are primarily used in ZIC which have shown issues related to low Zn deposition/stripping efficiencies, and Zn dendrites formation, resulting in device failure. To overcome these issues and to develop environmentally benign energy storage devices, here we have studied bio‐ionic liquid electrolytes (bio‐ILs) in both symmetric and asymmetric capacitors. Choline acetate (ChOAc) and betaine acetate (BetOAc) in water were investigated as electrolytes for capacitors in the presence and absence of Zn salts. Spectroscopic analysis showed that Zn solvation in the electrolytes changes significantly with the change in cation which affects the electrochemical reactions and capacitor performance. Raman analysis showed the Zn complex formed in the case of ChOAc is [Zn(OAc)4]2− whereas for BetOAc is [Zn(OAc)5]3− thereby the Zn deposition/stripping in ChOAc‐based electrolyte is quite stable whereas in case of BetOAc, Zn deposition/stripping is unstable. In the ChOAc electrolyte, the Zn/activated carbon asymmetric cell showed a capacity of >90 F g−1 at 0.1 A g−1 and a capacitance close to 40 F g−1 at 0.5 A g−1 with ∼82 % capacity retention after 3000 cycles, whereas BetOAc could only be used in symmetric cell capacitor. This study shows that bio‐ILs can be used as sustainable electrolytes in energy storage devices wherein the cation plays a significant role in the capacitor performance.